DIRECTIONS FOR DEVELOPMENT OF INNOVATIVE ENTREPRENEURSHIP IN ROSTOV-ON-DON - Yury V. Sitnikov (Advanced Engineering Research, 2011)
The development of the Russian national innovation system that is priority both for the science-and-technology sphere and for the competitive growth of the national economy is considered. The key component of the system is the commercialization of technologies as a part of the integral mechanism of the innovative development in the national innovation system, and in Rostov-on-Don in particular.